Strategi Penguatan Kelompok Tani di Desa Warnasari Kecamatan Pangalengan Kabupaten Bandung - Asifah Sri Rahayu; Dewi Rahmi (Bandung Conference Series: Economics Studies, 2022)
Abstract. Agricultural development is an effort to improve the quality of life of farming communities, which is achieved by the development of agricultural institutions. Institutional development can be done by strengthening farmer groups which aims to increase productivity and directly affect the welfare of farmers. Warnasari Village, Pangalengan District is an area that has good agricultural potential. However, there is still a lack of competitive farmers and there is a need for farmer groups to act as a forum to broaden farmers' horizons regarding new innovations in agriculture that can be studied through strengthening farmer groups. This type of research is descriptive quantitative, using survey research and primary data from interviews consisting of 26 people as samples taken from expert samples. The analytical method used is SWOT analysis which includes Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS) to determine the strongest strategy which is the main priority to be implemented in strengthening farmer groups. The results showed that the identification of key factors of farmer groups in Warnasari Village contained 9 internal strength factors, 9 internal weakness factors, 6 external opportunity factors and 6 external threat factors. In general, the condition of farmer groups in Warnasari Village is in a strong position internally and can effectively take advantage of potential opportunities and at the same time minimize the negative effects of potential external threats. The strategy generated by the analysis is the SO strategy. The use of digital technology, comparative studies and the implementation of programs that are in line with the government are the main strategies and become priorities to be implemented. Abstrak. Pembangunan pertanian merupakan upaya peningkatan kualitas hidup masyarakat tani, yang dicapai pengembangan kelembagaan pertanian. Pengembangan kelembagaan dapat dilakukan dengan adanya penguatan kelompok tani yang bertujuan untuk meningkatkan produktivitas dan secara langsung mempengaruhi kesejahteraan petani. Desa Warnasari, Kecamatan Pangalengan merupakan daerah yang memiliki potensi pertanian yang baik. Namun, masih kurang petani yang berdaya saing serta perlu adanya kelompok tani yang berperan sebagai wadah untuk memperluas wawasan petani mengenai inovasi baru dalam bidang pertanian yang dapat dikaji melalui penguatan kelompok tani. Jenis penelitian ini adalah deskriptif kuantitatif, menggunakan jenis penelitian survey dan data primer hasil wawancara yang terdiri dari 26 orang sebagai sampel yang diambil dari sampel expert. Metode analisis yang digunakan adalah analisis SWOT yang meliputi Internal Factors Analysis Summary (IFAS) dan External Factors Analysis Summary (EFAS) untuk menentukan strategi paling kuat yang menjadi prioritas utama untuk dijalankan dalam penguatan kelompok tani. Hasil penelitian menunjukan bahwa identifikasi faktor kunci dari kelompok tani di Desa Warnasari terdapat adanya 9 faktor kekuatan internal, 9 faktor kelemahan internal, 6 faktor peluang eksternal serta 6 faktor ancaman eksternal. Secara umum kondisi kelompok tani di Desa Warnasari berada dalam posisi kuat secara internal dan dapat efektif memanfaatkan potensi peluang serta sekaligus meminimalkan pengaruh negatif dari potensi ancaman eksternal yang ada. Strategi yang dihasilkan analisis tersebut adalah strategi SO. Pemanfaatan teknologi digital, studi banding dan penerapan program yang sesuai dengan pemerintah merupakan strategi yang utama dan menjadi prioritas untuk dijalankan.